Conformity on moral, social conventional and decency issues in the United Kingdom and Kuwait. (23rd September 2021) - Alshaalan, Hessah; Gummerum, Michaela
Abstract : Theories in moral psychology have debated whether people's moral judgements are influenced by social processes, such as others' opinions, arguments, and actions. This research investigated conformity with moral, social conventional and decency issues in adults from the United Kingdom (Study 1, N  = 50) and Kuwait (Study 2, N  = 164). Participants first had to make individual judgements regarding moral, social conventional and decency transgressions. Using a conformity paradigm with low social presence, 5–10 days afterwards participants were presented with the judgements of a more permissive majority. British participants conformed to the majority for decency, and to a lesser extent moral, transgressions. Kuwaiti participants conformed across domains. Furthermore, females in Kuwait conformed more than males. These findings are discussed with reference to the influence of cultural, moral and gender norms on conformity. Furthermore, we consider the contributions of these findings in light of theories of moral judgement and conformity.